Performance Feedback and Peer Effects - Marie Claire Villeval (Global Labor Organization (GLO), 2020)
This paper reviews studies conducted in naturally-occurring work environments or in the laboratory on the impact of performance feedback provision and peer effects on individuals' performance. First, it discusses to which extent feedback on absolute performance affects individuals' effort for cognitive or motivational reasons, and how evaluations can be distorted strategically. Second, this paper highlights the positive and negative effects of feedback on relative performance and rank on individuals' productivity and persistence, but also on the occurrence of anti-social behavior. Relative feedback stimulates effort by informing on the marginal return or the marginal cost of effort, and by activating behavioral forces even in the absence of monetary incentives. These behavioral mechanisms relate to self-esteem, status concerns, competitive preferences and social learning. Relative feedback sometimes discourages or distorts effort, notably if people collude or are disappointment averse. In addition to incentive schemes and social preferences, the management of self-confidence affects the way relative feedback impacts productivity. Third, the paper addresses the question of the identification of peer effects on employees' performance, their size, their direction and their heterogeneity along the hierarchy. The mechanisms behind peer effects include conformism, social pressure, rivalry, social learning and distributional preferences, depending on the presence of payoff externalities or technological and organizational externalities. ****** ERRATUM: On page 16, the reference "Alos-Ferrer, Segarra and Ritschel 2018" should be "Alos-Ferrer, Garcia-Segarra and Ritschel 2018". ******
Additional information: ERRATUM: On page 16, the reference "Alos-Ferrer, Segarra and Ritschel 2018" should be "Alos-Ferrer, Garcia-Segarra and Ritschel 2018".
Keywords: C9; D91; J3; M5; 330; Feedback; performance; peer effects